2023
DOI: 10.21831/jitp.v10i1.52930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zoom fatigue on health and learning loss in students during the COVID-19 pandemic

Abstract: Covid-19 pandemic causes all face-to-face activities converted to distance or virtual meetings, including educational learning system. These days, the majority educational institutions in Indonesia still implement distance learning via video conference platforms. This primary research aims to discover how Zoom Fatigue affects health and causes learning loss in university students across Java. The methodologies used in this research are qualitative and quantitative. To specify this research, the population is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The decline in students' comprehension and academic skills also occurs at the senior secondary level and the equivalent (Hanafiah et al, 2022;Rajib & Puspita Sari, 2022;Salsabila et al, 2022;Saputra & Fernandes, 2023;Widyasari et al, 2022). Even more surprising, it seems that the level of tertiary education is not spared from the grip of the learning loss phenomenon (Assiddiqi & Soeryanto, 2021;Lismandasari & Farhan, 2022;Miftakhuddin et al, 2022;Permana et al, 2023;Satriani & Khoirul Anwar, 2023;Subandowo et al, 2021). Furthermore, it can be concluded that this alarming phenomenon occurs at all levels of education.…”
Section: Teaching and Learning During The Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in students' comprehension and academic skills also occurs at the senior secondary level and the equivalent (Hanafiah et al, 2022;Rajib & Puspita Sari, 2022;Salsabila et al, 2022;Saputra & Fernandes, 2023;Widyasari et al, 2022). Even more surprising, it seems that the level of tertiary education is not spared from the grip of the learning loss phenomenon (Assiddiqi & Soeryanto, 2021;Lismandasari & Farhan, 2022;Miftakhuddin et al, 2022;Permana et al, 2023;Satriani & Khoirul Anwar, 2023;Subandowo et al, 2021). Furthermore, it can be concluded that this alarming phenomenon occurs at all levels of education.…”
Section: Teaching and Learning During The Covid-19 Pandemicmentioning
confidence: 99%
“…The second obstacle is from the teacher or instructor who cannot operate online learning devices or technological equipments optimally (Lukas & Yunus, 2021). This is accompanied by online learning provided by the teacher which students feel does not provide meaningful input and instead seems boring, so that the hybrid learning material delivered by the teacher is not absorbed perfectly (Permana et al, 2023;Prawanti & Sumarni, 2020). The solution offered is that the education office provides counseling for teachers in overcoming problems using online learning tools, as well as combining aspects of online learning with thirdparty applications such as Schoology, Quizzizz, ICANDO and the like to overcome student boredom during the learning process (Siregar et al, 2023).…”
Section: The Risks and Challenges Of Implementing Hybrid And Blended ...mentioning
confidence: 99%
“…Previous research by (Permana et al, 2023) stated that in the learning process students experience a decrease in interest and concentration in learning but are guided by academic scores in face-to-face learning. Research (Solihat et al, 2022) that learning has an effect on student learning loss in learning.…”
Section: Introductionmentioning
confidence: 99%